2016
DOI: 10.1590/1983-40632016v4642781
|View full text |Cite
|
Sign up to set email alerts
|

Ramularia leaf spot severity and effects on cotton leaf area and yield1

Abstract: Cotton monoculture favors the development of diseases such as ramularia leaf spot, which causes early defoliation and boll rotting, thus decreasing yield. This study aimed at evaluating the severity of ramularia leaf spot and its effects on cotton leaf area and yield. The experiment was conducted in a triple (4 x 3 x 2) factorial design, consisting of four cultivars (FM940GLT, FM944GL, TMG42WS and TMG43WS), three thirds of the plant (lower, middle and upper) and two management conditions (with and without fung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…On the Ecuadorian coast, the cotton crop is affected by diseases such as damping off (Rhizoctonia solani), cotton anthracnose (Colletotrichum gossypii), and Boll rot (Diplodia gossypina) (Sión et al 1992). Other diseases, like Ramularia leaf spot (Ramulariopsis pseudoglycines), present in neighboring countries (Aquino et al 2008) and not yet reported in Ecuador, can negatively affect the leaf area of cotton plants and fiber yield (Ascari et al 2016;da Silva et al 2019). Despite the importance of these diseases, there is little bibliography about them in Ecuadorian cotton crops.…”
Section: Ramularia Leaf Spot and Boll Rot Are Affected Differently By...mentioning
confidence: 99%
“…On the Ecuadorian coast, the cotton crop is affected by diseases such as damping off (Rhizoctonia solani), cotton anthracnose (Colletotrichum gossypii), and Boll rot (Diplodia gossypina) (Sión et al 1992). Other diseases, like Ramularia leaf spot (Ramulariopsis pseudoglycines), present in neighboring countries (Aquino et al 2008) and not yet reported in Ecuador, can negatively affect the leaf area of cotton plants and fiber yield (Ascari et al 2016;da Silva et al 2019). Despite the importance of these diseases, there is little bibliography about them in Ecuadorian cotton crops.…”
Section: Ramularia Leaf Spot and Boll Rot Are Affected Differently By...mentioning
confidence: 99%
“…On the Ecuadorian coast, the cotton crop is attacked by diseases such as damping off (Rhizoctonia solani), anthracnose of cotton (Colletotrichum gossypii), and Boll rot (Diplodia gossypina) (Sión et al 1992). Others like Ramularia leaf spot (Ramulariopsis pseudoglycines) present in neighboring countries (Aquino et al 2008) and not yet reported in Ecuador, it can negatively affect the foliar area and ber yield in plants of the genus Gossypium (Ascari et al 2016;da Silva et al 2019). Despite the importance of these diseases in cultivation, I have studied little or nothing.…”
Section: Introductionmentioning
confidence: 99%
“…Kühn), anthracnose (Colletotrichum gossypii Southw), boll rot, and ramularia leaf spot (Sión et al, 1992;Palma-Zambrano et al, 2022). Diseases like Ramularia leaf spot can negatively affect cotton plants' leaf area and fiber yield (Ascari et al, 2016). Other diseases identified in cotton crops in other countries such as charcoal rot [Macrophomina phaseolina (Tassi) Goid], bacterial blight [Xanthomonas campestris pv.…”
Section: Introductionmentioning
confidence: 99%